Pengembangan Nilai-nilai Wayang Jemblung untuk Meningkatkan Self Regulation Mahasiswa BK Semester 8 di Universitas PGRI Argopuro Jember - Iqbal Elza Wardana; Mudafiatun Isriyah; Nailul Fauziyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Eighth-semester students who are working on their scientific projects often face academic pressures that lead to low levels of self-regulation, particularly in time management, learning consistency, and emotional control. This study aims to develop a self-regulation enhancement module based on the values of Wayang Jemblung using the Research and Development (R&D) approach with the ADDIE model, employing a Likert scale questionnaire, interviews, and product trials with eighth-semester students at Universitas PGRI Argopuro Jember. The validation results indicated that the module received 75% from media experts and 75% from material experts, both of which fall into the valid category, confirming its feasibility for use. Furthermore, field trials through pre-test and post-test showed an improvement in students’ self-regulation from the low category (61.6%) to the high category (73.4%), although detailed individual increases are not elaborated. Qualitative findings supported these results by highlighting the internalization of cultural values, enhanced self-control, and increased learning motivation. Therefore, the Wayang Jemblung-based module is declared valid, feasible, and effective for improving the self-regulation of eighth-semester students who are completing their scientific projects, and it produces practical outputs in the form of a guidance module and a scientific article ready for publication.